Methotrexate and etanercept-induced primary cutaneous CD4 positive small/medium-sized pleomorphic T-cell lymphoma - Han MA; Shu Qiu; Rongbiao Lu; Peiying Feng; Chun Lu (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Immunosuppressive drugs and biological agents may represent a potential risk of lymphoma development in patients with rheumatoid arthritis. But most cases are diffuse, large B-cell lymphomas. Primary cutaneous CD4+ small/medium-sized pleomorphic T-cell lymphoma, a provisional entity in the 2005 WHO-EORTC classification of cutaneous lymphomas, is only described in a limited number of reports. To our knowledge, our case is a rare instance of primary cutaneous CD4+ small/medium-sized pleomorphic T-cell lymphoma, after associated treatment with methotrexate and etanercept, in a patient with moderate rheumatoid arthritis who had undergone an orchidectomy incorrectly.